Clinical and anamnestic portrait of patient with genital prolapse - Liliya R. Toktar; Mekan R. Orazov; Milana S. Lologaeva; Dmitrii G. Ariutin; Irina A. Samsonova; Rustam F. Gaifullin; Shakhlo M. Dostieva; Zarina N. Kamarova (LLC "MEDIAFORMAT", 2023)
Background. Pelvic organ prolapse (POP) is one of the most common and poorly understood gynecological diseases that is reported in 60% of women, and this indicator shows no downward trend. There is still no consensus on etiology and pathogenesis of genital prolapse (GP), despite numerous studies and hypotheses. Determining predictors of POP, allocating groups at high risk are among the key links of preventive strategy for management of patients with POP. Aim. To expand the knowledge about the risk factors of POP, determine the clinical and anamnestic portrait of woman with genital GP. Methods. The prospective cohort study was carried out in 2018-2020 at the Department of Obstetrics and Gynecology with Perinatology Course, Institute of Medicine, Peoples' Friendship University of Russia. The study involved 110 patients divided into groups based on the GP severity (group I - vaginal prolapse, group II - incomplete uterine prolapse, group III - complete uterine prolapse). Results. When studying the patients' clinical and anamnestic characteristics, it was found that the groups were comparable based on all major parameters. There were significant age differences between patients (p<0.05): elderly women were most often found in the group with complete uterine prolapse (group III). There were no significant differences (p>0.05) in social status, tobacco smoking, allergic reactions to medication, BMI, menarche, menstruation duration in all groups. Assessment of parity showed that the groups were comparable. Evaluation of extragenital diseases showed that there was a predictably larger number of patients with hypertension in group III, which was reflected by significant inter-group differences (p<0.05). The analysis of comorbidities also revealed a relatively small share of women with varicose veins, osteochondrosis, bronchial asthma and chronic bronchitis, which was confirmed by the lack of significant differences (p>0.05). Conclusion. Allocation of groups at high risk of severe POP based on clinical and anamnestic predictors is the most important aspect of preven-tion and prediction of GP. Such targeted approach will make it possible to prevent prolapse progression to advanced stages and improve the out-comes of conservative and surgical treatment of patients.